Diseased cinema : plagues, pandemics and zombies in American movies - Alpert, Robert; Eisenberg, Merle; Mordechai, Lee (Edinburgh : Edinburgh University Press, 2024)
This volume discusses how the depiction of diseases in movies has changed over the last century and what these changes reveal about American culture.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on December 19, 2023).
JSTOR
Keywords: Diseases in motion pictures; Horror films -- United States -- History and criticism; Motion pictures -- United States -- History; Maladies au cinéma.; Cinéma -- États-Unis -- Histoire; Films d'horreur -- États-Unis -- Histoire et critique; PERFORMING ARTS / Film / History & Criticism; Diseases in motion pictures; Motion pictures; United States; Films, cinema; Performing Arts; History